MiR-27 as a prognostic marker for breast cancer progression and patient survival. - Wei Tang (Public Library of Science (PLoS), 2012)
Background MicroRNA-27a (miR-27a) is thought to be an onco-microRNA that promotes tumor growth and metastasis by downregulating ZBTB10. The potential predictive value of miR-27a was studied in breast cancer patients. Methods The expression of miR-27a and ZBTB10 was examined in 102 breast cancer cases using in situ hybridization (ISH) and immunohistochemistry techniques and were evaluated semi-quantitatively by examining the staining index. The Correlation of miR-27a and ZBTB10 expression was analyed by Spearman Rank Correlation. The association of miR-27a and ZBTB10 expression with clinicopathological characteristics was analyzed using the χ(2) test, and their effects on patient survival were analyzed by a log-rank test and the Kaplan-Meier method. Univariate and multivariate Cox regression analyses were used to evaluate the prognostic values of miR-27a and ZBTB10. Results miR-27a was markedly up-regulated in invasive breast cancers that expressed low levels of ZBTB10 (P<0.001). A reverse correlation between miR-27a and ZBTB10 was also observed in breast cancer tissue samples (r(s) = -0.478, P<0.001). Furthermore, the expression of miR-27a and ZBTB10 was significantly correlated with clinicopathological parameters, including tumor size, lymph node metastasis and distant metastasis (P<0.05), but not with receptor status. Patients with high miR-27a or low ZBTB10 expression tended to have significantly shorter disease-free survival times (57 months and 53 months, respectively, P <0.001) and overall survival times (58 months and 55 months, respectively, P <0.001). Univariate and multivariate analysis showed that both miR-27a and ZBTB10 were independent prognostic factors of disease-free survival in breast cancer patients (P <0.001), while only miR-27a was an independent predictor of overall survival (P <0.001). Conclusions High miR-27a expression is associated with poor overall survival in patients with breast cancer, which suggests that miR-27a could be a valuable marker of breast cancer progression.